2003
DOI: 10.1093/rheumatology/keg227
|View full text |Cite
|
Sign up to set email alerts
|

Association of birth weight with osteoporosis and osteoarthritis in adult twins

Abstract: Bone mass and especially BMC are highly associated with birth weight. These associations are accounted for mainly by environmental factors that are independent of maternal factors such as gestational age, maternal smoking and nutrition, and are largely mediated by skeletal size and particularly adult height. Birth weight does not appear to be a major influence on the later development of radiographic OA in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 38 publications
5
91
1
1
Order By: Relevance
“…The reported association between factors in the intrauterine environment and birth weight and the subsequent development of certain adult diseases may also introduce bias (MZ twins, in general, have a lower birth weight than DZ twins). Although it has been shown that birth weight is associated with adult weight, there is no evidence to support the association between birth weight and the development of OA in later life (31). Our twin subjects had no greater prevalence of knee OA than that in the general population (28).…”
Section: Discussioncontrasting
confidence: 64%
“…The reported association between factors in the intrauterine environment and birth weight and the subsequent development of certain adult diseases may also introduce bias (MZ twins, in general, have a lower birth weight than DZ twins). Although it has been shown that birth weight is associated with adult weight, there is no evidence to support the association between birth weight and the development of OA in later life (31). Our twin subjects had no greater prevalence of knee OA than that in the general population (28).…”
Section: Discussioncontrasting
confidence: 64%
“…Coupled with animal studies (13)(14)(15), these data suggest that birth size is controlled at least in part by the intrauterine environment rather than by the genetic inheritance from both parents. Finally, a recent study that examined the association of birth weight with bone mass in a twin study of Ͼ4000 women confirmed that bone mass and especially BMC were highly associated with birth weight in both monozygotic and dizygotic twins (16). These associations point to environmental rather than genetic factors underlying the observed relationships.…”
Section: Discussionmentioning
confidence: 84%
“…2 29 A recent twin study showed that birth weight was related to BMD, independently of maternal factors, but not independently of adult height and weight. 29 An association between family position and bone health does not seem to have been previously reported.…”
Section: Policy Implicationsmentioning
confidence: 85%